HUMAN, CHANGE AND URBANIZATION: RURAL COMMUNITIES DYNAMICS AS SOCIO-CULTURAL AND ECONOMIC RESOURCES - Sriyanto, Sriyanto (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2014)
Interaction between rural and urban generates a contradiction in economic, cultural, social, political and even symbols oflifestyle of rural communitieswhich perceive them as a cynical society.The development of information and technology has made an impact onshifting the rural community to modernity and transform the societythrough the elements of social resources. The increasing complexity of life has affected rural and urban interaction, human need to adjust to the advanced demands of life through means of education, socio-cultural, economics and technology. These aspects intensifythe interaction between the rural and the urban through the gravity of each region. Gravity model is used to enhance the role of each region to improve the socio-cultural and economic resources